Pseudo Youla–Kucera parameterization with control of the waterbed effect for local loop shaping. (December 2015) - Chen, Xu; Jiang, Tianyu; Tomizuka, Masayoshi
Abstract: This paper discusses a discrete-time loop shaping algorithm for servo enhancement at multiple wide frequency bands. Such design considerations are motivated by a large class of practical control problems such as vibration rejection, active noise control, and periodical reference tracking; as well as recent novel challenges that demand new design in the servo technologies. A pseudo Youla–Kucera parameterization scheme is proposed using the inverse system model to bring enhanced control at selected local frequency regions. Design methodologies are created to control the waterbed amplifications that come from the fundamental limitations of feedback control. Finally, simulation and experimental verification are conducted in precision control and semiconductor manufacturing.